„Hoc quidem iuris est” (Coll. 5.2.1.): A Collatio legum Mosaicarum et Romanarum szerzőségének kérdéséhez - Grüll, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The Collatio Legum Mosaicarum et Romanarum, or “Collation of the Laws of Moses and the Romans”, is one of the most perplexing works of late antiquity: a law book compiled in the fourth or fifth century – the date of the work is still a matter of controversy – by an anonymous editor who wanted to show the similarity between laws of Moses and the Roman laws. Citing first laws from the Pentateuchus – especially from the books of Exodus, Leviticus, and Deuteronomy which he believed were written by Moses – the anonymous Collator then compared corresponding passages from Roman jurists and from Roman laws to form discussions on sixteen topics such as homicide, adultery, homosexuality, incest, and cruelty towards slaves. While earlier scholars wrestled with dating the Collatio, the religious identity of the Collator, and the purpose of the work, this paper suggests that the Collator may have been a Jew writing in Rome in an attempt to draw pagan lawyers to seeing the connections between the highly esteemed and very ancient laws of Moses, the famous legislator of the Jews whom he called as a priest, and the laws of classical Roman jurists, such as Paulus, Ulpianus, Modestinus, and Papinianus.